Efficacy and safety of angiogenesis inhibitors combined with poly ADP ribose polymerase inhibitors in the maintenance treatment of advanced ovarian cancer: a meta-analysis - Huang, Renming; Ji, Feng; Huang, Leyi; Qin, Yueying; Liang, Zhiyu; Huang, Miaoyan; Li, Chunyan (Frontiers in Oncology, 2024)
IntroductionThis meta-analysis was performed to evaluate the efficacy and safety of angiogenesis inhibitors (Ais) combined with poly ADP ribose polymerase inhibitors (PARPi) in the maintenance treatment of advanced ovarian cancer (OC).Materials and methodsA systematic search was conducted in four databases (Pubmed, Embase, Web of Science, and Cochrane) for articles published from the inception of the databases until January 15, 2024. The focus of the search was on articles investigating the combination of Ais with PARPi in the maintenance treatment of ovarian cancer. Meta-analyses were conducted to assess the objective response rate (ORR), progression-free survival (PFS), overall survival (OS), and the risk of Grade ≥ 3 adverse events (Grade≥ 3 AEs).ResultsTotally nine studies were included for meta-analysis. The overall pooled ORR of Ais combined with PARPi was 57% (95% CI, 35% to 77%). Subgroup analyses showed that the ORR for patients with platinum-resistant recurrent ovarian cancer, platinum-sensitive recurrent ovarian cancer and newly diagnosed advanced ovarian cancer were 30% (95% CI, 12% to 52%), 70% (95% CI, 61% to 78%) and 59% (95% CI, 55% to 63%), respectively. The median PFS was 5.8 months (95% CI, 5.3 to 7.1), 12.4 months (95% CI, 10.6 to 13.2) and 22.4 months (95% CI, 21.5 to 24.2), respectively. The median OS was 15.5 months (95% CI, 12.3 to 24.8), 40.8 months (95% CI, 33.4 to 45.2) and 56.3 months (95% CI, 49.0 to 62.0), respectively. The rate Grade≥ 3 TRAEs rate was found to be 0.22 (95% CI, 0.13 to 0.33).ConclusionsOur results confirmed that PARPi plus Ais was a feasible and safe option for the maintenance treatment of advanced ovarian cancer. The combination therapy should be recommended as the first-line maintenance treatment for patients with advanced ovarian cancer. PARPi plus Ais yielded more favorable oncological prognosis for patients with platinum-sensitive recurrent ovarian cancer, compared to patients with platinum-resistant recurrent ovarian cancer.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024543590, identifier CRD42024543590.